2018
DOI: 10.1371/journal.pone.0194752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leukocyte-reduced platelet-rich plasma on osteoarthritis caused by cranial cruciate ligament rupture: A canine gait analysis model

Abstract: The goal of this study was to objectively assess the effect of a platelet-rich plasma (PRP) derivate in English bulldogs with stifle degenerative joint disease secondary to cranial cruciate ligament rupture (CCLR). We used a force platform and affixed electrogoniometers to measure peak vertical force (PVF), vertical impulse (VI), stance time (ST), and angular range of motion (AROM), from 12 lame client-owned English bulldogs with post-CCLR stifle joint abnormalities. The 12 affected subjects were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 33 publications
(30 reference statements)
1
40
0
Order By: Relevance
“…[7][8][9] Orthobiologic products (such as mesenchymal stem cells, bone marrow aspirate concentrate, and platelets rich products) are showing promise as safe and effective treatments for musculoskeletal diseases including osteoarthritis in people and animals. [10][11][12][13][14][15][16][17][18] Platelets possess anabolic and anti-inflammatory properties attributed to the delivery of various growth factors and cell signaling molecules that can modulate inflammation and promote tissue healing. 19,20 Because various methods exist to create different platelet-derived orthobiologics, we define platelet-rich plasma (PRP) as any product in which the concentration of platelets is increased relative to whole blood and partially or fully isolated from leukocytes and red cells within a plasma medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Orthobiologic products (such as mesenchymal stem cells, bone marrow aspirate concentrate, and platelets rich products) are showing promise as safe and effective treatments for musculoskeletal diseases including osteoarthritis in people and animals. [10][11][12][13][14][15][16][17][18] Platelets possess anabolic and anti-inflammatory properties attributed to the delivery of various growth factors and cell signaling molecules that can modulate inflammation and promote tissue healing. 19,20 Because various methods exist to create different platelet-derived orthobiologics, we define platelet-rich plasma (PRP) as any product in which the concentration of platelets is increased relative to whole blood and partially or fully isolated from leukocytes and red cells within a plasma medium.…”
Section: Introductionmentioning
confidence: 99%
“…15,[20][21][22] More recently, the use of platelet-rich products has been shown to help alleviate pain and/or improve function including objective gait analysis in dogs with both naturally occurring and experimental models of OA. [13][14][15][16]23 We hypothesized that a single intra-articular injection of pure PRP (no white or red cells within the product) into the more severely affected stifle would cause substantial positive changes in kinetic gait symmetry in dogs with unilateral or bilateral chronic osteoarthritis attributed to long-term (>12 months) naturally occurring cranial cruciate ligament disease. A validated pressuresensitive walkway system was employed at baseline and every 4 weeks for 12 weeks post-treatment to determine peak vertical force (PF) and vertical impulse (VI) normalized to body weight in all limbs and calculate selected modified symmetry indices based on prior literature from PVF.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human species show that pain relief lasts for more than six months [21]. On the contrary, one study in dogs showed how the PRP effect disappeared after this same study period [22]. This fact highlights the need to develop objective methods to assess the PRP level of efficacy and duration of effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…Authors associated this response to treatment to an anti-inflammatory activity of PRP rather than any effect on tissue anabolism or catabolism [32]. It has also been used as a part of surgical protocols, leading to a significant improvement in gait performance in the postoperative period [31,33]. V-PET is a platelet concentrate as well as conditioned plasma, which contain many autologous anti-inflammatory mediators and growth factors, reported to reduce pain and lameness scores and increase weight bearing in dogs with OA [27,28].…”
Section: Introductionmentioning
confidence: 99%